Penser l’humain et l’animal·e depuis la sexualité - Maïa Petoton (Glad!)
Based on a discursive analysis of the curricula of biology, this article aims to examine the participation of SVT’s programmatic discourse on sexuality in the construction of the concept of humanity. After tracing the historical introduction of the terms sexuality, procreation, and reproduction in the curricula, we will analyze how the differentiated use of the latter two terms contributes to producing a dichotomy between human procreation and animal reproduction. We will then analyze the discursive mechanisms through which women are constructed as females-above-all in the curricula. Finally, we will show how, by considering animal sexual behaviors as solely motivated by reproduction, SVT ensures the inscription of human sexuality within the dominant norms of gender, sexuality, and animality.